Cellular Recycling of Proteins in Seed Dormancy Alleviation and Germination - Oracz, Krystyna; Stawska, Marlena (Frontiers in Plant Science, 2016)
Each step of the seed-to-seed cycle of plant development including seed germination is characterized by a specific set of proteins. The continual renewal and/or replacement of these biomolecules are crucial for optimal plant adaptation. As proteins are the main effectors inside the cells, their levels need to be tightly regulated. This is partially achieved by specific proteolytic pathways via multicatalytic protease complexes defined as 20S and 26S proteasomes. In plants, the 20S proteasome is responsible for degradation of carbonylated proteins, while the 26S being a part of ubiquitin-proteasome pathway is known to be involved in proteolysis of phytohormone signaling regulators. On the other hand, the role of translational control of plant development is also well-documented, especially in the context of pollen tube growth and light signaling. Despite the current progress that has been made in seed biology, the sequence of cellular events that determine if the seed can germinate or not are still far from complete understanding. The role and mechanisms of regulation of proteome composition during processes occurring in the plant’s photosynthetic tissues have been well-characterized since many years, but in non-photosynthetic seeds it has emerged as a tempting research task only since the last decade. This review discusses the recent discoveries providing insights into the role of protein turnover in seed dormancy alleviation, and germination, with a focus on the control of translation and proteasomal proteolysis. The presented novel data of translatome profiling in seeds highlighted that post-transcriptional regulation of germination results from a timely regulated initiation of translation. In addition, the importance of 26S proteasome in the degradation of regulatory elements of cellular signaling and that of the 20S complex in proteolysis of specific carbonylated proteins in hormonal- and light-dependent processes occurring in seeds is discussed. Based on the current knowledge the model of cellular recycling of proteins in germinating seeds is also proposed.